Early meteoric diagenesis and porosity preservation: Stratigraphie traps in carbonate grainstones - Major, R.P. (Society of Petroleum Engineers, 2014)
It is well established that aragonite sediment can be rapidly cemented in near-surface diagenetic environments when exposed to meteoric (fresh) water. Indeed, there are published examples of calcite cementation of aragonite sediments that resulted in rocks hard enough to require a hammer for sampling, and some of these examples formed in time periods shorter than a human lifetime. Complete mineralogie stabilization requires longer time periods, although within meteoric phreatic lenses in humid environments alteration to 100 percent low-magnesium calcite can occur as quickly as 5, 000 years. Early lithification, especially lithification and complete mineralogie stabilization in paleophreatic lenses, has been demonstrated to produce zones within carbonate rocks that are more resistant to compaction and porosity destruction during burial than superjacent and subjacent rocks. Thus, early exposure to meteoric phreatic diagenesis is one mechanism for producing stratigraphie traps; that is, hydrocarbon reservoirs in which the trapping mechanism is not controlled by structural deformation. Copyright 2014, International Petroleum Technology Conference